A comparative study on optimisation of protein extraction methods for Saccharomonospora azurea - Fodor, István; Valasek, Andrea; Urbán, Péter; Kovács, Márk; Fekete, Csaba; Kerepesi, Ildikó (Acta Biologica Szegediensis, 2017)
To establish the optimal cell disruption and protein extraction protocol for achieving the most efficient whole-cell protein extraction of Saccharomonospora azurea, four commonly used methods (X-Press, bead-vortexing, freezing-throwing and TCA/acetone/phenol extraction) were compared. Total protein content, as well as 1D and 2D SDS-PAGE protein patterns were assayed in the extracts to study the efficacy of these methods. Accordingly, of the four methods the X-Press proved the most effective for all initial weight (maximum 21.523 ± 0.23 mg/ml protein) followed by TCA/acetone/phenol method (maximum 13.682 ± 0.15 mg/ml protein), while the effectiveness of the two other methods were substantially inferior (maximum 3.188 ± 0.03 mg/ml protein). The analysis of protein gels proved that the X-Press method revealed a protein pattern characterised by the presence of the highest number of protein bands (on average of 52 and 385, on 1D and 2D gels, respectively). The TCA/acetone/phenol extraction provided similar effectiveness for only 100-300 mg initial bacteria mass, whereas bead-vortexing produced maximum 35 and 227 separated protein bands, on 1D and 2D gels, respectively. It can be stated that of the four methods the X-Press was the most effective one for all initial weight of bacteria, while the TCA/acetone/phenol method provides interpretable results for the 100-300 mg weight-range of bacteria.